Development of Geography Microlearning Media Content Assisted by Instagram Platform to Learn Inland Waters for High School Students - Hisan, Linda Khoirotun; Mudzakir, Ahmad (CV Bumi Spasial, 2024)
This study aims to develop and evaluate the integration of Instagram into Geography education, specifically for enhancing the understanding of Inland Waters among high school students. The significance of this integration lies in the alignment with contemporary educational practices that embrace digital literacy to foster student engagement and learning. Employing the ADDIE model, the research focuses on the design and development stages to create microlearning content tailored for Instagram. The findings indicate that Instagram as a learning aid significantly boosts student engagement, as evidenced by interactive content that supports visualization of geographical concepts and processes. These interactions not only enhance students' comprehension but also make learning a dynamic and engaging process. This research underscores the potential of social media platforms like Instagram to transform educational practices by providing accessible, engaging, and effective learning environments. Future studies could further explore the scalability of this approach across different subjects and educational settings